MANAGEMENT OF CHRONIC DIARRHEA ASSOCIATED WITH PANCREATIC DISORDER IN A NINE-MONTH-OLD DOMESTIC CAT - Ni Putu Juni Ratna Dewi; Putu Gede Yudhi Arjentinia; Ida Ayu Dian Kusuma Dewi (Buletin Veteriner Udayana, 2025)
A nine-month-old local cat was diagnosed with chronic diarrhea accompanied by pancreatitis. This article aims to report a case of chronic diarrhea in a local cat associated with pancreatic dysfunction. The diagnosis was established based on anamnesis, clinical examination, and laboratory findings indicating impaired pancreatic function. The prognosis for this case was considered favorable. Management included administration of the probiotic Entero Secure BD® for 30 days (1 tablet/day), a low-fat diet using a specialized gastrointestinal feed, supplementation with Vitazym Plus® for seven days (½ tablet/day), and supportive therapy in the form of acupuncture performed once weekly for four weeks. After 30 days of treatment, the patient’s clinical condition showed significant improvement, as evidenced by more solid feces and reduced abdominal pain. This case demonstrates an association between pancreatitis and chronic diarrhea, which may mutually exacerbate gastrointestinal dysfunction. The owner was advised to conduct regular health check-ups to monitor gastrointestinal status and minimize the risk of recurrence or potential complications.